Export marketing management - Ward, James J., ed. (ITC UNCTAD/GATT GenevaCH, 1985)
This selection of articles and summaries discuss the export marketing process, some export market research techniques in key areas or difficult markets, export product strategy considerations, distribution policies, promotional techniques and pricing policies. Contains four case studies illustrating different policies and management problems solved in typical developing country environments.